Functionalized nanostructures for enhanced photocatalytic performance under solar light - Guo, Liejin; Jing, Dengwei; Liu, Maochang; Chen, Yubin; Shen, Shaohua; Shi, Jinwen; Zhang, Kai (Beilstein Journal of Nanotechnology, 2014)
Photocatalytic hydrogen production from water has been considered to be one of the most promising solar-to-hydrogen conversion technologies. In the last decade, various functionalized nanostructures were designed to address the primary requirements for an efficient photocatalytic generation of hydrogen by using solar energy: visible-light activity, chemical stability, appropriate band-edge characteristics, and potential for low-cost fabrication. Our aim is to present a short review of our recent attempts that center on the above requirements. We begin with a brief introduction of photocatalysts coupling two or more semiconductors, followed by a further discussion of the heterostructures with improved matching of both band structures and crystal lattices. We then elaborate on the heterostructure design of the targeted materials from macroscopic regulation of compositions and phases, to the more precise control at the nanoscale, i.e., materials with the same compositions but different phases with certain band alignment. We conclude this review with perspectives on nanostructure design that might direct future research of this technology.
Keywords: functionalized nanostructures; hydrogen; photocatalysis; photocatalytic; solar light